Development and Status of the Information Systems / Wirtschaftsinformatik Discipline. An Interpretive Evaluation of Interviews with Renowned Researchers: Part II - Results Information Systems Discipline - Carola Lange (Universität Duisburg-Essen, Institut für Informatik und Wirtschaftsinformatik (ICB), 2005)
This report presents the results of a partly explorative and partly hypotheses based interview study with eight renowned Information Systems researchers. The study was performed with the objective to re-construct the development and status of the discipline taking advantage of the diverse perspectives and experiences of respected researchers. They have been in the field from its beginning and have not only observed the field's development but have shaped it, for example through the initiation of conferences and associations, curriculum efforts and by establishing new Information Systems departments. The research results show, that the young Information Systems discipline aimed at overcoming the initial lack of academic legitimacy by adhering to business schools' requirements for scientific research. Today, academic credibility to a certain extent has been achieved through highly respected journals and business school support has increased. However, no significant research results that impacted practice could be identified and the Information Systems discipline is - by related disciplines - still not understood as having a valuable academic assignment.
Keywords: 650; Wirtschaftsinformatik; Hochschulforschung; Vergleich; Deutschland; Nordamerika